Antiphospholipid Antibodies Overlapping in Isolated Neurological Syndrome and Multiple Sclerosis: Neurobiological Insights and Diagnostic Challenges - D’Angelo, Chiara; Franch, Oriol; Fernández-Paredes, Lidia; Oreja-Guevara, Celia; Núñez-Beltrán, María; Comins-Boo, Alejandra; Reale, Marcella; Sánchez-Ramón, Silvia (Frontiers in Cellular Neuroscience, 2019)
Antiphospholipid syndrome (APS) is characterized by arterial and venous thrombosis, pregnancy morbidity and fetal loss caused by pathogenic autoantibodies directed against phospholipids (PL) and PL-cofactors. Isolated neurological APS may represent a significant diagnostic challenge, as epidemiological, clinical and neuroimaging features may overlap with those of multiple sclerosis (MS). In an open view, MS could be considered as an organ-specific anti-lipid (phospholipid and glycosphingolipid associated proteins) disease, in which autoreactive B cells and CD8+ T cells play a dominant role in its pathophysiology. In MS, diverse autoantibodies against the lipid-protein cofactors of the myelin sheath have been described, whose pathophysiologic role has not been fully elucidated. We carried out a review to select clinical studies addressing the prevalence of antiphospholipid (aPL) autoantibodies in the so-called MS-like syndrome. The reported prevalence ranged between 2% and 88%, particularly aCL and aβ2GPI, with predominant IgM isotype and suggesting worse MS prognosis. Secondarily, an updated summary of current knowledge on the pathophysiological mechanisms and events responsible for these conditions is presented. We draw attention to the clinical relevance of diagnosing isolated neurological APS. Prompt and accurate diagnosis and antiaggregant and anticoagulant treatment of APS could be vital to prevent or at least reduce APS-related morbidity and mortality.